Non-uniform extensional motions of materially non-uniform simple solids - Zahorski, S. (Archives of Mechanics, 1996)
Non-uniform extensional motions of materially non-uniform simple solids are considered in greater detail. These motions may be useful as applied to quasi-elongational motions with temperature and structure variations. In particular, the constitutive equations are discussed for steady drawing processes of polymer fibres.